An Attempt to Solving Non Linear Differential Equation: Exploring the Applications and Importance of Nonlinear Differential Equations (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In this article we present a structure for comprehension non-linear differential equation all the more better. Nonlinear differential equations have gotten a lot of enthusiasm because of its expansive applications. Nonlinear ordinary differential equations assume a significant job in numerous parts of connected and unadulterated science and their applications in building, connected mechanics, quantum material science, systematic science, stargazing and science.